2008
DOI: 10.1590/s0034-72992008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Incidência e evolução da polipose nasal em crianças e adolescentes com fibrose cística

Abstract: Nasal polyps are a clinical sign of alert for investigatingCystic Fibrosis (CF). Aims: To study the incidence of nasal polyps in children and adolescents with cystic fibrosis, its possible association with age, gender, clinical manifestations, genotype and sweat chlorine level, and its evolution with topical steroid therapy. Methods: Clinical symptoms, sweat chlorine level and genotype were studied in 23 cystic fibrosis patients. Nasal polyps were diagnosed by nasal endoscopy and treated with topical steroids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…From 1961 to 2005, the prevalence of nasal polyps increased from 5 to 57%. 26,29,[31][32][33][34][35][36][37][38][40][41][42] Explanations include increased survival rates of CF patients in developed countries, the selection of patients, sample sizes, different age groups in these studies, and especially the more recent routine use of nasal endoscopy as a diagnostic tool. 3,19,48 Brihaye et al 29 showed that over 25% of polyps were not diagnosed in the clinical examination with anterior rhinoscopy without nasal endoscopy in CF patients.…”
Section: Nasal Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…From 1961 to 2005, the prevalence of nasal polyps increased from 5 to 57%. 26,29,[31][32][33][34][35][36][37][38][40][41][42] Explanations include increased survival rates of CF patients in developed countries, the selection of patients, sample sizes, different age groups in these studies, and especially the more recent routine use of nasal endoscopy as a diagnostic tool. 3,19,48 Brihaye et al 29 showed that over 25% of polyps were not diagnosed in the clinical examination with anterior rhinoscopy without nasal endoscopy in CF patients.…”
Section: Nasal Endoscopymentioning
confidence: 99%
“…[28][29][30] The frequency of nasal polyposis varies in different populations, and depends on the evaluation technique. 26,29,[31][32][33][34][35][36][37][38][39][40][41][42] It is thought that nasosinusal involvement may worsen pulmonary manifestations; 20 thus, otorhinolaryngologists have become more involved in evaluating these patients. Recent studies in Brazil 26,40,41 have shown a growing concern with characterizing in more detail the nasosinusal findings of CF patients, because this disorder is genetically very heterogeneous, with many types of mutations and a wide variety of clinical presentations, 28 which may be explained by specific phenotypic features of the Brazilian population and even within populations of any given region in this country.…”
Section: Introductionmentioning
confidence: 99%
“…According to data from the literature and the study previously conducted in our service, 23 a need for better characterization of the evolution of UAW involvement in these patients was identified.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 , 30 The frequency of nasal polyposis varies in different populations, and depends on the evaluation technique. 26 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 …”
Section: Introductionmentioning
confidence: 99%
“…It is thought that nasosinusal involvement may worsen pulmonary manifestations; 20 thus, otorhinolaryngologists have become more involved in evaluating these patients. Recent studies in Brazil 26 , 40 , 41 have shown a growing concern with characterizing in more detail the nasosinusal findings of CF patients, because this disorder is genetically very heterogeneous, with many types of mutations and a wide variety of clinical presentations, 28 which may be explained by specific phenotypic features of the Brazilian population and even within populations of any given region in this country.…”
Section: Introductionmentioning
confidence: 99%